TEKNOLOGI MEMBRAN FILTRASI AIR RAWA/GAMBUT BERBASIS PANEL SURYA UKM PENGOLAH IKAN ASIN DESA MUNING BARU - dodon turianto nugrahadi; Totok Wiyanto; Sri Cahyo Wahyono; Ahmad Rusadi Arrahimi; sholih Afif (Jurnal Pengabdian Kepada Masyarakat (MEDITEG), 2022)
River water and well water are the main sources for the daily water needs for the people of South Kalimantan. However, the peatland water has a muddy and smelly that has an effect on health. This cloudy and smelly condition is due to the condition of the peatlands in the South Kalimantan region. The use of peat water by the community in Muning Baru Village, South Daha, HSU has been carried out for a long time, especially UKM salted fish processing. The quality and quantity of fish production are affected by the quality of clean water. Implementation begins with the design of the filtration membrane, assembly of solar panels, pumps and filtration tubes. It is hoped that this application will support the society towards society 5.0. The results of the implementation are giving the needs of clean water up to 80%, either else NTU 30 become 3.44 NTU, TSS 522 mg/l become 352 mg/l, COD 31.9 mgO2 /l become 6.09 mg02/l.